Local antituberculosis treatment in nonhealing chronic surgical site tuberculosis: A novel approach to cure nonhealing wound! - Shital Patil; Deepak Patil; Shubhangi Khule; Gajanan Gondhali (Annals of Medical Science and Research)
Tuberculosis most commonly affects the lungs and less than 20% of cases showed extrapulmonary involvement. Tuberculosis at the surgical site is described in the medical literature with very few cases of cesarean section at the incision site. Nonhealing surgical site ulcers secondary to tuberculosis are not widely reported in the literature and treatment options to heal these lesions are not described. Surgical site infections resulting to a slow or nonhealing wound are commonly reported and usually depend on various factors. Patient factors include the patient’s immune status and comorbidities. Hospital management factors such as infection control policies in operation theatre, sterilization techniques for surgical instruments, and local wound care methods established and implemented by hospital staff. In this case report, a 34-year-old female with history of cesarean delivery 1 month back presented with nonhealing wound at the surgical site. We have done surgical repair with biopsy of wound margins. Wound discharge microscopy was negative for acid fast bacilli with few gram-positive cocci. Cartridge based nucleic acid amplification testes were positive for Mycobacterium tuberculosis genome. Histopathology shown tuberculous pathology and underlying chronic infectious process for nonhealing wound. We have offered antituberculosis treatment (ATT) as per protocol and observed healing of tuberculous ulcer after three months with reappearance of ulcer in fourth month of ATT. We have topically applied isoniazid and streptomycin over tuberculous ulcer along with systemic ATT. Tuberculous ulcer has responded and noted “cure” as completely healed surgical wound after 6 months of ATT with topical application of isoniazid and streptomycin.